The impact of human development on the economy of Saudi Arabia in view of the vision 2030 during (1990 – 2016) - Al- Abdullah, Nada Shadad; Al- Ghamdi, Reem Saeed (Journal of Economic, Administrative and Legal Sciences, 2020)
The study examined the effect of human development in Saudi Arabia within the vision 2030 during the period (1990- 2016) relationship between the sexes, where the variable GDP of both (labor force, life expectancy at birth, average income, economic openness) According to UNDP, overall price level (human development (life expectancy at birth, expenditure on education, average income) and economic growth. Among the results of the annual non- significant study (manpower, economic openness, the general level of prices), and in the light of these results, we reached a set of the most important: expansion and intensification of investment in education, training and rehabilitation, and activation to the Saudization of the economy, and rationalize government spending in line with development needs Economic.
Keywords: economic growth; human development; Saudi Arabia; spending on education